BOTRROID Embryonal Rhabdomyosarcoma with Uterine Cervix in a Postmenopausal Woman: An Unusual Case Report - Saeed Karimkhani; Monireh Mirzaie; Soheila Sarmadi; Zahra Kolangdari (Wolters Kluwer Medknow Publications, 2024)
Rhabdomyosarcoma (RMS) is one of the most common soft-tissue sarcomas that engage the embryonal skeletal muscle cells as the female reproductive tract. Embryonal RMS (ERMS) is the most prevalent subtype of RMS in the female genital tract. Botryoid RMS is a rapidly growing rare malignancy and a polypoid variant of ERMS that occurs in childhood and constituting approximately 3% of all RMSs among young children and 1% among adolescents and young adults. A 50 year old menopause woman who had been vaginal discharge and bleeding for about 2 years without dysuria, dyspareunia, or postcuital bleeding was informed consent for presenting. A vaginal examination, pathology examination, sonography, magnetic resonance imaging, immunohistochemistry, surgery and radical hysterectomy, radiation therapy, and two sessions of brachytherapy were performed. After 22 months of follow-up, the patient had no evidence of recurrence or any problem in sexual activity. Oncological surgical treatment based on the carcinoma site and adjuvant chemotherapy is helpful for the treatment of RMS. However, applying the standard treatment guidelines is essential, although it is very scarce and difficult.